2008
DOI: 10.1007/s00436-008-1022-4
|View full text |Cite
|
Sign up to set email alerts
|

Acaricidal activity of the hyacinthacine analogues derived from pyrrolizidine alkaloids on Rhipicephalus (Boophilus) microplus

Abstract: This study reports the effect of six hyacinthacine analogues derived from pyrrolizidine alkaloids on egg hatchability and mortality rates of newly hatched larvae of the cattle tick Rhipicephalus (Boophilus) microplus. All the compounds were toxic to the larvae of the ticks and inhibited the eggs hatchability in the higher concentration tested (5 microg/ml). Even in the lowest concentration (0.625 microg/ml), some effect in the eggs hatchability was observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
(11 reference statements)
0
2
0
Order By: Relevance
“…After 24 h of treatment, the highest acaricidal activity of 70.8% was recorded in the ticks treated with 8% extract of A. squamosa followed by Nicotiana tobacum (45.8%) and Tamarindus indica (41.7%) extracts, while 29.8% and 20.8% mortality, respectively, was recorded in ticks treated with Eucalyptus globulus and Citrus limonum extracts against B. microplus (Magadum et al 2009)). Duarte et al (2008) have reported that effect of six hyacinthacine analogues derived from pyrrolizidine alkaloids were toxic to the larvae of the ticks and inhibited the eggs' hatchability at 5 μg/ml, and at the lowest concentration (0.625 μg/ml), some effect in the eggs' hatchability was observed against the cattle tick R. (B.)…”
Section: Discussionmentioning
confidence: 98%
“…After 24 h of treatment, the highest acaricidal activity of 70.8% was recorded in the ticks treated with 8% extract of A. squamosa followed by Nicotiana tobacum (45.8%) and Tamarindus indica (41.7%) extracts, while 29.8% and 20.8% mortality, respectively, was recorded in ticks treated with Eucalyptus globulus and Citrus limonum extracts against B. microplus (Magadum et al 2009)). Duarte et al (2008) have reported that effect of six hyacinthacine analogues derived from pyrrolizidine alkaloids were toxic to the larvae of the ticks and inhibited the eggs' hatchability at 5 μg/ml, and at the lowest concentration (0.625 μg/ml), some effect in the eggs' hatchability was observed against the cattle tick R. (B.)…”
Section: Discussionmentioning
confidence: 98%
“…All the larvae died at concentrations between 5.5 and 7.14% [34). Duarte et al [35] have reported that effect of six hyacinthacine analogues derived from pyrrolizidine alkaloids were toxic to the larvae of the ticks and inhibited the eggs' hatchability at 5μg/ml. The plant Sapindus saponaria also demonstrated larvicidal activity for the Rhipicephalus sanguineus (Acari: Ixodidae), with LC50 and LC99 values of 1,994 and 3,922 ppm, respectively [36].…”
Section: Discussionmentioning
confidence: 99%
“…Several potentially therapeutic effects of hyacinthacine have been reported. For example, analogues of hyacinthacine are acaricidal, at least in vitro,7 and other actions have been described both in vitro and in animals.…”
Section: Hyacinthacinementioning
confidence: 99%